2016
DOI: 10.1016/j.ifacol.2016.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Optimal Energy Management of Electrified Engines

Abstract: The electrification of engine components offers significant opportunities for fuel economy improvements, including the use of an electrified turbocharger for engine downsizing and exhaust gas energy recovery. By installing an electrical device on the turbocharger, the excess energy in the air system can be captured, stored, and re-used. This new configuration requires a new control structure to manage the air path dynamics. The selection of optimal setpoints for each operating point is crucial for achieving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The ETA was developed by a consortium led by Caterpillar. Based on the ETA, several control methods and testing systems were developed in Loughborough University in simulations [23]- [25] and experiments [26]. The tracking performance of the proposed 3-input 3-output (3I3O) controller at 1800 rpm, 260 Nm is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ETA was developed by a consortium led by Caterpillar. Based on the ETA, several control methods and testing systems were developed in Loughborough University in simulations [23]- [25] and experiments [26]. The tracking performance of the proposed 3-input 3-output (3I3O) controller at 1800 rpm, 260 Nm is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Energy management for a balanced SOC is another critical aspect of EATC control. Several researchers have concluded that, 6,11 in order to have the ability to Figure 1. Schematic of the EATC assisted diesel engine with DEMG.…”
Section: Improved Regulation Of Intake Oxygen Concentra-mentioning
confidence: 99%
“…Glenn et al proposed a sliding mode controller while considering VGT–EGR interactions but did not discuss SOC management. 8 Zhao et al proposed a two-layer energy management strategy, 11 where the supervisory control generates optimized target values for pre-turbine pressure, boost pressure, and compressor mass flow rate, to be tracked by the low-level controller. Their approach, however, relied on an extensive pre-calibrated map of the pressure upstream of the turbine for reference generation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, a consortium led by Caterpillar Inc. developed a cutting-edge electrified turbocharger called electric turbo assist (ETA). Based on the ETA, several control methods and testing systems were developed in Loughborough University in simulations [17]- [19] and experiments [20]- [23]. This paper analyzes the dynamics of the ETDE.…”
Section: Introductionmentioning
confidence: 99%